Development and Validation of a Rapid Method for Identification of New Synthetic Cannabinoids in Hair Based on High-Performance Liquid Chromatography–Ion Trap Mass Spectrometry Using a Simplified User Interface. Issue 1 (10th May 2022) - Musile, Giacomo; Palacio, Covadonga; Murari, Matilde; Appolonova, Svetlana; Tagliaro, Franco
Abstract: The penetration of the new psychoactive substances (NPSs) into the market of clandestine drugs is highly dynamic, causing potentially false-negative results using the current analytical instrumentation, particularly in the screening phase. At present, the suggested approach to perform a comprehensive screening requires the use of high-resolution mass spectrometry (MS) with associated high costs of purchase and maintenance and need of skilled and dedicated personnel. Here we describe the development and validation of a simplified approach based on a high-performance liquid chromatography–ion trap MS system with a user-friendly interface dedicated to toxicological analysis. The system, originally intended for a broad toxicological screening, was tuned to identify new synthetic cannabinoids in hair. After a washing step with dichloromethane, hair (about 50 mg) was incubated for 3 h with 1.5 mL ethanol. One milliliter of this solution was then dried, reconstituted with mobile phase and injected. The peak identification was based on the chromatographic retention times and MS2/MS3 data using a database which included up to 158 NPSs. The method was validated according to international guidelines on a selected panel of NPSs, namely methyl 2-[[1-(5-fluoropentyl)indazole-3-carbonyl]amino]-3, 3-dimethylbutanoate (5F-ADB), 1-Pentyfluoro-1H-indole-3-carboxylic acid 8-quinolinyl ester (5F-PB 22), N-[(2S)-1-amino-3-methyl-1-oxobutan-2-yl]-1-(5-chloropentyl)indazole-3-carboxamide (5Cl-AB-PINACA), (S)-N-(1-amino-1-oxo-3-phenylpropan-2-yl)-1-(5-fluoropentyl)-1H-indole-3-carboxamide [5F-APP-PICA (PX-1)], : (R)-N-(1-amino-1-oxo-3-phenylpropan-2-yl)-1-(5-fluoropentyl)-1H-indazole-3-carboxamide [5F-APP-PINACA (PX-2)], N-[(2S)-1-Amino-3-methyl-1-oxobutan-2-yl]-1-(cyclohexylmethyl)indazole-3-carboxamide (AB-CHMINACA), N-[(2S)-1-Amino-3-methyl-1-oxobutan-2-yl]-1-[(4-fluorophenyl)methyl] indazole-3-carboxamid (AB-FUBINACA), methyl (2S)-2-[[1-(cyclohexylmethyl)indole-3-carbonyl]amino]-3, 3-dimethylbutanoate (MDMB-CHMICA), (S)-Methyl 2-(1-(5-fluoropentyl)-1H-indole-3-carboxamido)-3-methylbutanoate (MMB-2201) and (1-pentylindol-3-yl)-(2, 2, 3, 3-tetramethylcyclopropyl)methanone (UR-144). The tested analytical method showed detection limits between 0.065 and 0.125 ng/mg. The intraday imprecision of the method showed average values within the range of 7.3–20%. The estimation of the trueness (bias) of method showed average values within the range of 1.5–12.3%. The analytical performance was also successfully assessed by four proficiency test samples containing NPS. No synthetic cannabinoids were detected in application to 82 hair samples from forensic cases previously analyzed with liquid chromatography–MS triple quadrupole.